PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 1 RENGAT - Shidiq, Muhamad Zaenul Anwar Shidiq Zaenul Anwar; Murni, Atma Murni; ', Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This is a pre-experimental study that aims to determine the effect of the application of problem-solving strategies in Think Pair Share (TPS) structural approach of cooperative learning for mathematics learning outcomes (MLO) which include attitudes, knowledge, and skills competences. This research was conducted in grade VII SMP Negeri 1 Rengat on odd semester Academic Year (AY) 2014/2015 with the subject matter of numbers pattern. This study design using Intec Group Comparison. The population in this study is the seventh grade students of SMP Negeri 1 Rengat AY 2014/2015. Samples in this study involved three groups were selected by purposive sampling technique, each of as many as 35 students, VIIB as the first experimental class following study with problem solving strategies in TPS structural approach of cooperative learning (PSSTPS), VIID as the second experimental class following the TPS structural approach of cooperative learning (TPSCL), and VIIC as the controll class following conventional learning (CL). The MLO data of attitude competence taken using self-assessment techniques, whereas knowledge and skills competences taken using math achievement test. This study showed the following results. (1) There are differences in MLO of skills and knowledge competences among learners who follow PSSTPS and learners who follow CL. (2) There are differences in MLO of knowledge competence among learners who follow TPSCL and learners who follow CL. (3) There is no difference in MLO of knowledge and skills competences among learners who follow PSSTPS, TPSCL, and PK in addition to those mentioned in (1) and (2). Key Words: Problem solving strategies, Think Pair Share structural approach to Cooperative learning, mathematical achievement